2018
DOI: 10.1103/physreva.98.013855
|View full text |Cite
|
Sign up to set email alerts
|

Topological Floquet edge states in periodically curved waveguides

Abstract: We study the Floquet edge states in arrays of periodically curved optical waveguides described by the modulated Su-Schrieffer-Heeger model. Beyond the bulk-edge correspondence, our study explores the interplay between band topology and periodic modulations. By analysing the quasienergy spectra and Zak phase, we reveal that, although topological and non-topological edge states can exist for the same parameters, they can not appear in the same spectral gap. In the highfrequency limit, we find analytically all bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 46 publications
(69 reference statements)
0
17
0
Order By: Relevance
“…As such, our gauge‐induced interface modes are different from other modulation‐induced defect states. [ 54–56 ]…”
Section: Discussionmentioning
confidence: 99%
“…As such, our gauge‐induced interface modes are different from other modulation‐induced defect states. [ 54–56 ]…”
Section: Discussionmentioning
confidence: 99%
“…Considering the periodic boundary condition, we have ψ l1,l2+Lt = ψ l1+Lt,l2 = ψ l1,l2 . Due to the time periodicity, we can express the probability amplitudes ψ l1l2 (t) by the Fourier components [11,24]…”
Section: B Frequency-domain Analysismentioning
confidence: 99%
“…Periodic modulation not only provides a versatile tool to manipulate the quantum particles, but also brings novel states of matter into the quantum systems [9]. It has already been utilized to control the hopping [10,11], band structure [12,13], and quantized transport of a single particle [14][15][16][17][18][19]. Remarkably, artificial gauge field [20] and Floquet topological insulator [21][22][23] have been realized by well-designed modulation protocols.…”
Section: Introductionmentioning
confidence: 99%
“…By arraying the waveguides with alternating interval, the Floquet Su-Schrieffer-Heeger (SSH) model can be mimicked. Theoretical study found that zero modes and π modes, which are localized at the end of the one dimensional lattice, can be generated by the Floquet engineering [37][38][39][40][41][42]. The localized modes have been observed in experiment [43,44].…”
Section: Introductionmentioning
confidence: 99%